Still a 'Force for Good'? Good International Citizenship in British Foreign and Security Policy. (14th January 2014) - Gilmore, Jonathan
Research Highlights and Abstract Through an analysis of recent foreign policy discourse, in particular the UK approach to stabilisation, the article identifies distinctive similarities and continuities in the patterns of ethically‐minded foreign policy, employed by the 1997–2010 Labour government and the Conservative‐Liberal Democrat Coalition. The article makes a fresh engagement with the concept of Good International Citizenship, arguing for a much more overt engagement, by policymakers, with the concept, to help address some of the shortcomings associated with both Labour and the Coalition's attempts to incorporate ethical obligations into British foreign policy. This article examines the interaction between the idea of Good International Citizenship and the recent evolution of UK foreign and security policy. Good International Citizenship centres on the mediation of ethical commitments to national interest, to the promotion international order, and to the wellbeing of vulnerable non‐citizen populations. Whilst ethical commitments to non‐citizens have become overt components of British foreign policy, recent UK governments have struggled to reconcile these with commitments to the national interest and a stable international order. The article argues that the more direct affirmation of Good International Citizenship as a narrative and ethos of practice for UK foreign policy might help further the increasingly open discussion on the ethics and UK foreign policy. As a framework for dialogue and public debate, the concept provides a means by which ethical commitments in the traditionally closed world of foreign policy might be opened up to wider critical scrutiny.